A review of renewable energy potential in Nigeria; solar power development over the years - Olusola Bamisile (Engineering and Applied Science Research, 2017)
Nigeria is one of most populated countries in the world. With a population of about 170 million people, the nation is enriched with diverse renewable and non-renewable energy sources. Despite this huge energy potential, only about 50% of her population have access to electricity. The main objective of this review is to present and analyze the renewable energy potentials of Nigeria with special attention and consideration to the past, present and future of solar energy development. The country aims to achieve electricity production of 9.74%, 18% and 20% of her electricity from renewables by 2015, 2020 and 2030, respectively. Solar energy is expected to produce 1.26%, 6.92% and 15.27% of the electricity consumed by 2015, 2020 and 2030, respectively. If these targets are met, the proportion of the population with access to electricity will increase drastically. Data collected from various reputable energy sources and Journals are reviewed. Nigeria has renewable energy resources including biomass, wind, hydropower and solar energy. These resources can sufficiently meet the country’s energy demands, but statistics show that Nigeria still lacks adequate supplies to meet her electricity demands. The policies put in place to meet her energy targets and the current status of the country’s supply and demand for electricity are discussed in detail.